Flattening the curve - London, Martha (Core library guide to Covid-19, 2021)
As the COVID-19 pandemic spread, the phrase "flatten the curve" became widely known. It refers to the things people can do to space the total number of infections out over a longer period of time. This helps prevent the health-care system from being overloaded. Flattening the Curve examines social distancing and the other measures that people took to slow the spread of the disease.